2018
DOI: 10.1111/auar.12236
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Litigation Risk Increase on Big N Auditor Exits and Audit Quality in the Korean Savings Banking Industry

Abstract: This study investigates whether an increase in litigation risk results in Big N auditors leaving the industry and examines the impact of this increase on audit quality. Using a sample of Korean savings banks from 2009 to 2015, the study finds that the proportion of Big N auditors sharply decreases after a savings bank crisis, suggesting that Big N auditors are likely to reject riskier clients, while audit quality is unchanged. The results provide new evidence that an increase in litigation risk does not necess… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 57 publications
(103 reference statements)
0
3
0
1
Order By: Relevance
“… Archival research shows this joint feature (Big 4 and designated auditor) in ADS firms (see Jung & Kim, 2019). …”
mentioning
confidence: 99%
“… Archival research shows this joint feature (Big 4 and designated auditor) in ADS firms (see Jung & Kim, 2019). …”
mentioning
confidence: 99%
“…Prior research has shown that higher litigation risk regimes result in higher audit quality and higher audit fees. Jung and Kim () show that in the face of increased litigation risk (i.e., a banking crisis) rather than increase audit quality, large audit firms are more likely to reject risker clients.…”
Section: Audit Qualitymentioning
confidence: 99%
“…Overall, all the research converges towards a common result, auditors being sued provide higher audit quality because they have more wealth at risk in case of litigation. Thus, the topic of audit litigation is studied, not as a consequence of poor quality audit, but rather as an upstream risk that should be sought to prevent [96]. Causes of auditor litigation [81] Archival 147 firms that were subject to class action lawsuits naming auditors / U.S Issuing a going concern report reduces litigation risk in general, but increases litigation risk when it is issued for financially stressed clients.…”
Section:  Audit Quality Attributes and Auditor Litigationmentioning
confidence: 99%